Identification of the β thalassemia allele β–50 and analysis of the hematology data of carriers in a southern Chinese population. (24th September 2021) - Long, Ju; Liu, Enqi
Abstract: During a routine test, we identified a 38‐year‐old man who had a positive hematology screening result but was negative for hot spot variants of his thalassemia gene. Further analysis identified β –50 (HBB: c.‐100G>A). It was first suggested that β –50 was a β + ‐thal allele, and some research groups suggested this allele was a silent β‐thal allele. To fully understand the hematological phenotype of the β –50 allele, we screened for individuals carrying β –50 in the general population and performed hematology analysis on these carriers. A real‐time PCR detection system was designed to verify samples carrying β –50 . Twenty‐one thousand samples and 43 pedigree samples were screened, and 86 β –50 carriers were detected. We performed hematological analysis on 65 individuals older than 3 years who had normal serum ferritin and analyzed the data. A total of 34.62% of the β –50 /β N individuals had mean cellular volume (MCV) or mean cellular hemoglobin (MCH) values slightly lower than the positive cutoff value of screening; the β –50 carriers' Hb A2 value was slightly elevated. According to the test results, β –50 carriers have slight changes in hematology parameters, including slight decreases in MCV and MCH and slight increases in Hb A2 ; however, these effects do not reach the degree of traditional β + alleles. Females with genotype β –50 /β 0 show a degree of decline in hematological indicators during pregnancy. Therefore, we should describe β –50 as a β ++ thalassemia allele, and identification of β –50 can explain slight changes in hematological indicators in some carriers.